Cyclic shear fatigue of orthodontic brackets bonded to enamel using self-adhering flowable composites - Tariq Abu Haimed; Reham Osama Filfilan; Mawadah Nazih Hassoubah; Ensanya A. Abou Neel; Mohamed Bamashmous (Elsevier, 2023)
Background: Self-adhering composites are claimed to bond to teeth without prior acid etching and bonding steps. This study aimed to evaluate the cyclic shear fatigue (CSF) of metal orthodontic brackets bonded to enamel using self-adhering flowable composites (Constic and VertiseTM Flow) in comparison with that of total-etch and self-etch adhesives. Materials and methods: Twenty-five human premolars comprising 100 surfaces were randomly divided into four groups (n = 25): total-etch, self-etch, Constic, and VertiseTM Flow. A total of 10 surfaces were used per group for baseline static shear bond strength (SSBS) evaluation and 15 surfaces for CSF evaluation. Each tooth was treated with the four bonding agents. Both SSBS and CSF were evaluated using a universal testing machine. For CSF, the staircase method was used with an initial pulling load equivalent to 60% of the SSBS of each group for 1000 cycles or until failure. The adhesive remaining index (ARI) was evaluated for surviving samples using a stereomicroscope. Statistical analysis: A one-way ANOVA with Tukey's post hoc test was used to analyze the CSF data, and a chi-square test was used to analyze the ARI. Results: The total-etch adhesive showed significantly higher CSF values than that of the other groups (p < 0.001). Both total-etch (10.78 ± 0.31 MPa) and self-etch (6.75 ± 0.91 MPa) adhesives showed significantly higher CSF than did Constic (1.94 ± 0.31 MPa) and VertiseTM Flow (2.01 ± 0.25 MPa), (p < 0.001). The ARI indicated that more resin remnants were observed with the total-etch and self-etch adhesives than those with the self-adhering flowable composites. However, no significant differences were observed among groups (p > 0.05). Conclusions: Total-etch and self-etch adhesives showed satisfactory bond strengths for orthodontic treatment. However, Constic and VertiseTM Flow self-adhering flowable composites may not be clinically sufficient for bonding metallic orthodontic brackets to enamel.